Analysis and integration of multilevel inverter configuration with boost converters in a photovoltaic system - Prabaharan, N.; Palanisamy, K. (Energy conversion and management, 2016)
[Display omitted] •Integration of MLI with boost converters in photovoltaic system including MPPT.•Results are taken for different irradiations and different temperature condition.•Proposed system is tested with sudden step changes from standard test condition.•Analysis of switching losses and conduction loss is discussed.•Theoretical calculation of % THD using asymptotic formula is discussed. This paper proposes a single phase multilevel inverter configuration that conjoins three series connected full bridge inverter and a single half bridge inverter for renewable energy application especially photo-voltaic system. This configuration of multilevel inverter reduces the value of total harmonic distortion. The half bridge inverter utilized in the proposed configuration increases the output voltage level to nearly twice the output voltage level of a conventional cascaded H-bridge multilevel inverter. This higher output voltage level is generated with lesser number of power semiconductor switches compared to conventional configuration, thus reducing the total harmonic distortion and switching losses. The effectiveness of the proposed configuration is illustrated by replacing the isolated DC sources in multilevel inverter with individual photo-voltaic panels using separate perturb and observer based maximum power point tracking and boost converters. The verification of the proposed system is demonstrated successfully using MATLAB/Simulink based simulation with different irradiation and temperature conditions. Also, the transient operation of the system is verified with results depicted using step change in standard test condition. In the proposed system, total harmonic distortion of the output voltage is 9.85% without using passive filters and 3.91% with filter inductance. Theoretical calculation of the power losses and total harmonic distortion with mathematical equations are discussed. Selective experimental results are presented to prove the effectiveness of proposed system.